Quality problems as process safety warning signs. Issue 2 (24th April 2013) - Herber, John W.
<x xml:space="preserve">Abstract</x> Many companies collect and report process safety incidents. Some companies also collect process safety near misses. These safety near misses are sometimes quality deviations; for example, a process parameter that exceeds the safe operating limit, a critical safety system that is activated, or a minor release of hazardous material occurs. The intent of this article is to show how a quality incident can also be a process safety near‐miss and what should be done to recognize its potential severity. Many of the causes of quality problems may be subtle, such as the fouling of cooling surfaces or a control valve that responds slowly. If these issues continue unchecked, the conditions will continue to persist and a more serious event occurs. © 2013 American Institute of Chemical Engineers Process Saf Prog, 2013